2016
DOI: 10.5498/wjp.v6.i1.177
|View full text |Cite
|
Sign up to set email alerts
|

White matter alterations in anorexia nervosa: A systematic review of diffusion tensor imaging studies

Abstract: AIM:To identify findings concerning white matter (WM) fibre microstructural alterations in anorexia nervosa (AN). METHODS:A systematic electronic search was undertaken in several databases up to April 2015. The search strategy aimed to locate all studies published in English or Spanish that included participants with AN and which investigated WM using diffusion tensor imaging (DTI). Trials were assessed for quality assessment according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…Furthermore, loss of white matter integrity correlated with the number of BE episodes(58), indicating a potential link between reduced myelination and increased symptomatic severity. White matter pathology was also observed in in the brains of anorexic patients exhibiting restricted food intake(60, 61). Furthermore, rodents restrict chow intake between intermittent binge episodes of limited access to PF(62-64).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, loss of white matter integrity correlated with the number of BE episodes(58), indicating a potential link between reduced myelination and increased symptomatic severity. White matter pathology was also observed in in the brains of anorexic patients exhibiting restricted food intake(60, 61). Furthermore, rodents restrict chow intake between intermittent binge episodes of limited access to PF(62-64).…”
Section: Discussionmentioning
confidence: 98%
“…Although the evidence shows changes in WM in the AN population, there are no unequivocal results in the literature, and data as for FA modifications in subcortical regions in AN population is still preliminary (Barona et al, ; King et al, ; Monzon et al, ). In fact, from our analysis we hypothesized that we would extend previous studies and find further evidence for reduced FA in AN in structures that are involved in affective and body image processing (Treasure et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, no consideration was made as for the problem of PVE regarding the alteration of FA (Seitz, 2017). The same limitations can also be highlighted also in previous articles, where a strict selection of the clinical population was not carried out, with subsequent mixed results (King et al, 2018;Monzon, Hay, Foroughi, & Touyz, 2016).The anatomic likelihood estimation (ALE) is a robust voxel-based metaanalysis method used to examine the consistency of the results across various neuroimaging studies (Turkeltaub, Eden, Jones, & Zeffiro, 2002). It is based on the convergence of spatial peak coordinates across studies and provides a model based on a quantitative analysis of the reviewed results.…”
Section: Introductionmentioning
confidence: 99%
“…DTI studies of acutely ill patients with AN have generally shown microstructural WM alterations (Monzon, Hay, Foroughi, & Touyz, 2016), although specific findings are mixed. For adult patients, studies point to decreased FA (Frieling et al, 2012;Hayes et al, 2015;Kazlouski et al, 2011;Nagahara et al, 2014;Via et al, 2014), which in some instances is accompanied by increased MD (Nagahara et al, 2014;Via et al, 2014).…”
mentioning
confidence: 99%